Melanoma vaccines: current R&D landscape, translational hurdles, and future outlook—a perspective drawn from 442 clinical trials - Gao, Canni; Duan, Xinxin; Peng, Leixuan; Zhao, Yixin; Li, Pan; Mou, Kuanhou (Frontiers in Immunology, 2026)
BackgroundMelanoma, a highly malignant skin tumor with high metastatic propensity and poor survival in advanced stages, poses a major global public health challenge, as conventional treatments have notable limitations. Tumor immunotherapy, particularly cancer vaccines, has emerged as a promising approach by activating/regulating immune mechanisms to target cancer cells.MethodsThis study systematically searched the Trialtrove database for interventional clinical trials of melanoma and cancer vaccines up to August 5, 2025. After screening via inclusion/exclusion criteria, 442 trials were analyzed, adhering to PRISMA guidelines with independent dual review for data reliability.ResultsTrials were geographically concentrated in developed regions (69% in the US), with minimal participation from Asia, Africa, and Latin America. A “translational funnel effect” was observed: Phase I/I-II trials accounted for 63.6%, while Phase III trials only 6.1%, with a 22.9% termination rate. Peptide/recombinant protein vaccines (186 trials) and cellular vaccines (151 trials) were mainstream, with nucleic acid vaccines (58 trials) as a promising emerging platform. Combination therapy (227 trials, >50%), especially with immune checkpoint inhibitors (ICIs), dominated; adjuvants (e.g., IL-2, GM-CSF agonists) enhanced efficacy. Most trials focused on Stage III/IV patients (91.1%): key trials showed mRNA-4157 + pembrolizumab reduced recurrence/death risk by 49% in resected melanoma, and herpes simplex virus RP1 + nivolumab achieved 58.3% objective response rate (ORR) in ICI-resistant patients. Primary endpoints favored safety/immunogenicity (215/142 trials), with overall survival (OS, 33 trials) rarely used; academic institutions led funding (52.3%).ConclusionsMelanoma vaccines, especially in combination with ICIs and via personalized platforms, have significant potential. However, challenges include tumor heterogeneity, immunosuppressive tumor microenvironment (TME), inefficient delivery, geographical R&D imbalance, and low Phase III conversion. Interdisciplinary collaboration, international multicenter trials, optimized clinical design (e.g., early-stage patient enrollment), and policy support are needed to advance their clinical translation.